Riding the rapids: COVID‐19, the three rivers curriculum, and the experiences of the University of Pittsburgh School of Medicine. Issue 5 (24th February 2021) - Elnicki, D. Michael; Drain, Peter; Null, Greg; Rosenstock, Jason; Thompson, Ann
ABSTRACT: When faced with the COVID‐19 pandemic this past spring, the University of Pittsburgh's School of Medicine (UPSOM) took rapid steps to ensure the safety of students, staff, and the faculty as well as to maintain the educational process. Curriculum reform efforts, already underway, proved to be an advantage in the transformation. We quickly converted to a remote and then a hybrid curriculum. Research labs were reopened with appropriate safety measures. Clinical experiences for students restarted via a phased process that emphasized safety and graduation requirements. A variety of assessment mechanisms were restarted with appropriate modifications. New teaching models, such as flipped classrooms, have become the norm, and it seems hard to imagine our returning to our old pedagogy. The curriculum committee met continually to guide the process of change and reopening. The curricular adaptation process remains ongoing, and challenges remain. Nonetheless, we have learned from our experiences and hope to use this knowledge gained as we move forward.